1971
DOI: 10.1136/bmj.2.5759.430
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Subdural Haematoma and its Relationship to Whiplash Injuries

Abstract: SummarySubdural haematoma is one of the commonest features of the battered child syndrome; yet by no means all the patients so affected have external marks of injury on the head. This suggests that in some cases repeated acceleration/deceleration rather than direct violence is the cause of the haemorrhage, the infant having been shaken rather than struck by its parent. Such an hypothesis might also explain the remarkable frequency of the finding of subdural haemorrhage in battered children as compared with its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
127
1
8

Year Published

1972
1972
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(137 citation statements)
references
References 4 publications
(1 reference statement)
1
127
1
8
Order By: Relevance
“…5,6 Guthkelch, a British neurosurgeon, first postulated that the cause of SDH in Battered Child Syndrome was a shaking injury, causing rotational forces within the cranium which disrupted vessels bridging the subdural space. 7 He commented that, at the time, a 'good shaking' was considered by many British parents socially more acceptable and less dangerous than a blow to the head.…”
mentioning
confidence: 99%
“…5,6 Guthkelch, a British neurosurgeon, first postulated that the cause of SDH in Battered Child Syndrome was a shaking injury, causing rotational forces within the cranium which disrupted vessels bridging the subdural space. 7 He commented that, at the time, a 'good shaking' was considered by many British parents socially more acceptable and less dangerous than a blow to the head.…”
mentioning
confidence: 99%
“…9) Holbourn understood that the deformable brain was incompressible, hypothesized a rotational acceleration level beyond which injury would occur, and that a smaller mass of brain would require larger rotational acceleration. Ommaya himself alluded to this point in his paper, 16) although this seems not to have been recognized by Guthkelch,8) Caffey, 2,3) and others. In 1987 Duhaime et al, 7) using available data on scaled injury thresholds, demonstrated that shaking a mechanical model to cause intracranial injury in the form of concussion, subdural hematoma, and diffuse axonal injury, failed to reach such Shaken Baby Syndrome: An Odyssey thresholds.…”
Section: Injury Biomechanicsmentioning
confidence: 95%
“…Ommaya found intracranial injury in 18 of the animals, with concomitant neck injury in 11 of the 18. The purely isolated concept of rotational acceleration of sufficient magnitude to cause intracranial injury without impact and therefore without external evidence of injury was seized upon qualitatively by Guthkelch,8) Caffey,2,3) and others as the explanation for hitherto unexplained intracranial injury in infants. This concept was hypothesized and put forth by them as being the result of manual shaking.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In 1962, Henry Kempe described the clinical signs of physical abuse of children and was the first to present the "battered child syndrome" concept (3). Shaken infant syndrome was first described by Guthkelch and then by Caffey in the beginning of 1970s (4,5). The pioneering work of these doctors marked the major milestones for the detection of child abuse cases, and they raised awareness on this issue.…”
Section: Introductionmentioning
confidence: 99%